THE INFLUENCE OF SOCIAL ECONOMIC LAW ON SOCIAL WELFARE: LITERATURE REVIEW AND POLICY IMPLICATIONS - Sapta Nur Fallah; Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This study examines the impact of social economy law on social welfare through a comprehensive review of existing literature and analyses relevant policy implications. Social economy law plays an important role in addressing economic injustice and inequality and improving people's welfare through various mechanisms such as resource redistribution and social protection. With proper design and implementation, social economy law-based policies can eflectively reduce economic disparities and provide support to vulnerable groups, creating a more inclusive and just society. The research also highlights the importance of synergy between various stakeholders in policy formulation and implementation, as well as the need for institutional and administrative strengthening to achieve the desired results. The findings ofler valuable insights for policymakers in their endeavour to sustainably improve social welfare.